Frequency, causes, and factors of maternal mortality in the City of Bunia, North East of the Democratic Republic of the Congo - Clarice Ngavele; B. Mukandu; M. O. Omanyondo (Orapuh Journal)
Introduction Mortality among pregnant women is a significant public health issue. Every day, approximately 830 women die worldwide due to complications during pregnancy or childbirth.